Facial feedback affects valence judgments of dynamic and static emotional expressions - Hyniewska, Sylwia; Sato, Wataru (Frontiers in Psychology, 2015)
The ability to judge others’ emotions is required for the establishment and maintenance of smooth interactions in a community. Several lines of evidence suggest that the attribution of meaning to a face is influenced by the facial actions produced by an observer during the observation of a face. However, empirical studies testing causal relationships between observers’ facial actions and emotion judgments have reported mixed findings. This study is the first to measure emotion judgments in terms of valence and arousal dimensions while comparing dynamic versus static presentations of facial expressions. We presented pictures and videos of facial expressions of anger and happiness. Participants (N = 36) were asked to differentiate between the gender of faces by activating the corrugator supercilii muscle (brow lowering) and zygomaticus major muscle (cheek raising). They were also asked to evaluate the internal states of the stimuli using the affect grid while maintaining the facial action until they finished responding. The cheek-raising condition increased the attributed valence scores compared with the brow-lowering condition. This effect of facial actions was observed for static as well as for dynamic facial expressions. These data suggest that facial feedback mechanisms contribute to the judgment of the valence of emotional facial expressions.